2013
DOI: 10.3892/ijo.2013.1892
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of human prostatic stromal cells in primary cultures derived from human tissue samples

Abstract: Abstract.Emerging evidence has shown that the tumor microenvironment plays a crucial role in prostate cancer (PCa) development and progression. However, the mechanism(s) through which stromal cells regulate epithelial cells and the differences among prostatic stromal cells of different histological/pathological origin in PCa progression remain unclear. Therefore, it is necessary to characterize the stromal cell populations present in benign prostatic hyperplasia (BPH) and PCa. To this end, we used cultures fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…Additionally, the percentage of myofibroblasts in high-grade prostate cancer derived primary cultures was higher than in moderate and low grade cancer (41), confirming the importance of CAFs in tumor formation and progression. Prostate cancer is characterized by a reactive stroma that is enriched with fibroblasts and myoblasts (42).…”
Section: Discussionmentioning
confidence: 68%
“…Additionally, the percentage of myofibroblasts in high-grade prostate cancer derived primary cultures was higher than in moderate and low grade cancer (41), confirming the importance of CAFs in tumor formation and progression. Prostate cancer is characterized by a reactive stroma that is enriched with fibroblasts and myoblasts (42).…”
Section: Discussionmentioning
confidence: 68%
“…The stromal cells from BPH tissues may be characterized by properties that allow the infiltration and retention of secreted proteins that are not evident in prostate cancer stromal cells. Others have shown that BPH stromal cells are more fibroblastic, while prostate cancer stromal cells are more myofibroblastic . Additionally, BPH and prostate cancer typically occur in different anatomic locations, which may also play a role in the presence of secreted proteins in BPH stroma.…”
Section: Discussionmentioning
confidence: 99%
“…Anti α‐SMA and anti‐vimintin were used to determine the stromal cell populations by Immunofluorescence. After three to four passages, a homogeneous stromal cell population was established …”
Section: Methodsmentioning
confidence: 99%